Leveraging AI technologies for preventing and detecting sudden cardiac arrest and death - Pradeep, Nijalingappa, 1977-; Kautish, Sandeep, 1981-; Ghonge, Mangesh, 1984-; Ravi, Renjith, 1985- (Medical Information Science Reference, 2022)
"This book discusses how AI technologies can assist physicians to make better clinical decisions enabling early detection of subclinical organ dysfunction, through the use of clinically relevant information that can be found in the massive amount of data and, thus, improving quality and efficiency of healthcare delivery"--